Connecting urban green spaces: the importance of irregular settlements in biodiversity and peri-urban planning - Risty Khoirunisa; Eka Permanasari; Muhamad Risqi U. Saputra; Maria H. Hällfors; Michaela F. Prescott; Alex M. Lechner (Urban Ecosystems, 2026)

Enhancing urban forest connectivity: a multispecies modelling approach in Helsinki - Julia Hämäläinen; Alex M. Lechner; Johan Ekroos; Jiawei Zhao; Susanna Lehvävirta (Urban Ecosystems, 2026)
Understanding how landscape elements contribute to functional connectivity in a multispecies context is important to inform city planning. We compared the connectivity of urban forest habitats for three vertebrate species with contrasting dispersal modes: the Siberian flying squirrel ( Pteromys volans ), the common lizard ( Zootoca vivipara ) and European crested tit ( Lophophanes cristatus ). We used Graphab and Circuitscape, combined with literature- and expert opinion-based parameters to model their dispersal potential. We compared these models with designated existing connections and rerun the models with modelled future connections by the city of Helsinki, Finland. Our results suggest that despite the relatively high share of forests in Helsinki as compared to many capital cities in Europe and beyond, lack of connectivity may disrupt the movement in different ways for all three species. Isolation was mainly a result of either lack of habitat or too scarce connectivity elements combined with high landscape resistance. Isolation varied depending on species’ specific habitat requirements, interpatch-crossing distance and gap-crossing distance. Based on our models of functional connectivity, the designated existing connections were excessively optimistic. The modelled future connections enhanced connectivity, especially if created with sufficient quality for each species, yet only a small fraction of the modelled future connections was realistically convertible as pathways. Nevertheless, our approach can inform city planning by identifying critical connections and places, where strengthening or building functional connectivity would be beneficial. We suggest that city’s green wedges should be converted into a webbed urban green space network.

Balancing landscape values and tourism choices: Integrating participatory mapping and the IPBES Values Typology - Liliana Solé; Kyle P. Hearn; Tahjudil Witra; Alex M. Lechner; Nora Fagerholm (Ambio, 2025)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) Biosphere Reserves aim to balance nature and human coexistence, but increasing tourism challenges landscape management. The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) stresses the importance of understanding stakeholder values for effective management of natural spaces through a typology of intrinsic, instrumental, and relational values. This study applies this IPBES typology to tourism preferences in the Archipelago Sea Biosphere Reserve (ABR) using Public Participation Geographic Information Systems (PPGIS). A 2022 survey gathered data from 690 locals, recreationists, and tourists revealing intrinsic values as the most significant. Locals prioritized intrinsic and relational values, while recreationists and tourists emphasized relational and instrumental values. The study highlights a preference for small-scale tourism that preserves landscapes and heritage, illustrating the complexity of aligning stakeholder values in tourism and conservation. Insights from this research guide policymaking to better accommodate diverse values in protected areas.

Multi-modal deep learning approaches to semantic segmentation of mining footprints with multispectral satellite imagery - Muhamad Risqi U. Saputra; Irfan Dwiki Bhaswara; Bahrul Ilmi Nasution; Michelle Ang Li Ern; Nur Laily Romadhotul Husna; Tahjudil Witra; Vicky Feliren; John R. Owen; Deanna Kemp; Alex M. Lechner (Remote Sensing of Environment, 2025)

First records of diurnal and nocturnal predatory birds from artificial hunting perch trials in oil palm plantations - Kamil Tohiran; Dzulhelmi Muhammad Nasir; Maisarah Burhanuddin; Frisco Nobilly; Raja Zulkifli; Ramle Moslim; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (BioControl, 2024)

Corrigendum to “Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data” [Urban For. Urban Green. 98 (2024) 128415] - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Mapping development preferences on the perceived value of ecosystem services and land use conflict and compatibility in Greater Kuala Lumpur - Karen T. Lourdes; Chris N. Gibbins; Ben C. Sherrouse; Darius J. Semmens; Perrine Hamel; Ruzana Sanusi; Badrul Azhar; Jay Diffendorfer; Alex M. Lechner (Urban Forestry & Urban Greening, 2024)

Increasing mine waste will induce land cover change that results in ecological degradation and human displacement - John R. Owen; Deanna Kemp; Alex M. Lechner; Michelle Ang Li Ern; Éléonore Lèbre; Gavin M. Mudd; Mark G. Macklin; Muhamad Risqi U. Saputra; Tahjudil Witra; Anthony Bebbington (Journal of Environmental Management, 2024)

Mapping public support for urban green infrastructure policies across the biodiversity-climate-society -nexus - Jussi Lampinen; Oriol García-Antúnez; Alex M. Lechner; Anton Stahl Olafsson; Natalie M. Gulsrud; Christopher M. Raymond (Landscape and Urban Planning, 2023)

Identifying indicator bird species for sustainable oil palm plantation certification - Zulkifli Nursyamin; Muhammad Syafiq Yahya; Sharifah Nur Atikah; Kamil Azmi Tohiran; Ahmad R. Norhisham; Nurul Wahida Othman; Alex M. Lechner; Badrul Azhar (Journal of Cleaner Production, 2023)

Global assessment of the biodiversity safeguards of development banks that finance infrastructure - Divya Narain; Laura J. Sonter; Alex Mark Lechner; James E. M. Watson; Jeremy S. Simmonds; Martine Maron (Conservation Biology, 2023)
Infrastructure development is a major driver of biodiversity loss globally. With upward of US$2.5 trillion in annual investments in infrastructure, the financial sector indirectly drives this biodiversity loss. At the same time, biodiversity safeguards (project‐level biodiversity impact mitigation requirements) of infrastructure financiers can help limit this damage. The coverage and harmonization of biodiversity safeguards are important factors in their effectiveness and therefore warrant scrutiny. It is equally important to examine the extent to which these safeguards align with best‐practice principles for biodiversity impact mitigation outlined in international policies, such as that of the International Union for Conservation of Nature. We assessed the biodiversity safeguards of public development banks and development finance institutions for coverage, harmonization, and alignment with best practice. We used Institute of New Structural Economics and Agence Française de Développement's global database to identify development banks that invest in high‐biodiversity‐footprint infrastructure and have over US$500 million in assets. Of the 155 banks, 42% ( n = 65) had biodiversity safeguards. Of the existing safeguards, 86% (56 of 65) were harmonized with International Finance Corporation (IFC) Performance Standard 6 (PS6). The IFC PS6 (and by extension the 56 safeguard policies harmonized with it) had high alignment with international best practice in biodiversity impact mitigation, whereas the remaining 8 exhibited partial alignment, incorporating few principles that clarify the conditions for effective biodiversity offsetting. Given their dual role in setting benchmarks and leveraging private finance, infrastructure financiers in development finance need to adopt best‐practice biodiversity safeguards if the tide of global biodiversity loss is to be stemmed. The IFC PS6, if strengthened, can act as a useful template for other financier safeguards. The high degree of harmonization among safeguards is promising, pointing to a potential for diffusion of practices.

Reforestation could bring native mammal species back in the tropical highlands - Siti Wahdaniyah; Ku Noor Khalidah; Nabilah Hamidah Sabar; Norizah Kamarudin; Ruzana Sanusi; Norhisham Ahmad Razi; Alex M. Lechner; Badrul Azhar (Tropical Ecology, 2023)

Smallholder oil palm plantation sustainability assessment using multi-criteria analysis and unmanned aerial vehicles - Yong Bin Wong; Chris Gibbins; Badrul Azhar; Su Shen Phan; Paul Scholefield; Reza Azmi; Alex M. Lechner (Environmental Monitoring and Assessment, 2023)
Oil palm agriculture has caused extensive land cover and land use changes that have adversely affected tropical landscapes and ecosystems. However, monitoring and assessment of oil palm plantation areas to support sustainable management is costly and labour-intensive. This study used an unmanned aerial vehicles (UAV) to map smallholder farms and applied multi-criteria analysis to data generated from orthomosaics, to provide a set of sustainability indicators for the farms. Images were acquired from a UAV, with structure from motion (SfM) photogrammetry then used to produce orthomosaics and digital elevation models of the farm areas. Some of the inherent problems using high spatial resolution imagery for land cover classification were overcome by using texture analysis and geographic object-based image analysis (OBIA). Six spatially explicit environmental metrics were developed using multi-criteria analysis and used to generate sustainability indicator layers from the UAV data. The SfM and OBIA approach provided an accurate, high-resolution (~5 cm) image-based reconstruction of smallholder farm landscapes, with an overall classification accuracy of 89%. The multi-criteria analysis highlighted areas with lower sustainability values, which should be considered targets for adoption of sustainable management practices. The results of this work suggest that UAVs are a cost-effective tool for sustainability assessments of oil palm plantations, but there remains the need to plan surveys and image processing workflows carefully. Future work can build on our proposed approach, including the use of additional and/or alternative indicators developed through consultation with the oil palm industry stakeholders, to support certification schemes such as the Roundtable on Sustainable Palm Oil (RSPO).

Potential of agroforestry orchards as a conservation set-aside initiative in industrial rubber tree and oil palm plantations for avian biodiversity - Muhammad Syafiq Yahya; Sharifah Nur Atikah; Izereen Mukri; Aslinda Oon; Ainil Hawa; Ruzana Sanusi; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (Biodiversity and Conservation, 2023)

Large‐scale reforestation can increase water yield and reduce drought risk for water‐insecure regions in the Asia‐Pacific - Hoong Chen Teo; Srivatsan V. Raghavan; Xiaogang He; Zhenzhong Zeng; Yanyan Cheng; Xiangzhong Luo; Alex M. Lechner; Matthew J. Ashfold; Aakash Lamba; Rachakonda Sreekar; Qiming Zheng; Anping Chen; et al. (Global Change Biology, 2022)
Large‐scale reforestation can potentially bring both benefits and risks to the water cycle, which needs to be better quantified under future climates to inform reforestation decisions. We identified 477 water‐insecure basins worldwide accounting for 44.6% (380.2 Mha) of the global reforestation potential. As many of these basins are in the Asia‐Pacific, we used regional coupled land‐climate modeling for the period 2041–2070 to reveal that reforestation increases evapotranspiration and precipitation for most water‐insecure regions over the Asia‐Pacific. This resulted in a statistically significant increase in water yield ( p

Evaluating the experimental cultivation of edible mushroom, Volvariella volvacea underneath tree canopy in tropical agroforestry systems - Nurul Kamaliah; Sabiha Salim; Sumaiyah Abdullah; Frisco Nobilly; Sapari Mat; Ahmad R. Norhisham; Kamil Azmi Tohiran; Raja Zulkifli; Alex M. Lechner; Badrul Azhar (Agroforestry Systems, 2022)

Landscape-scale Remote Sensing and Classification of Lentic Habitats in a Tropical City - Hoong Chen Teo; Matthew J. Hill; Alex M. Lechner; Fang Yenn Teo; Christopher N. Gibbins (Wetlands, 2021)

Measuring fire severity using UAV imagery in semi-arid central Queensland, Australia - Phill McKenna; Peter D. Erskine; Alex M. Lechner; Stuart Phinn (International Journal of Remote Sensing, 2017)

The Sensitivity of Population Viability Analysis to Uncertainty about Habitat Requirements: Implications for the Management of the Endangered Southern Brown Bandicoot - DARREN M. SOUTHWELL; ALEX M. LECHNER; TERRY COATES; BRENDAN A. WINTLE (Conservation Biology, 2008)
Whenever population viability analysis (PVA) models are built to help guide decisions about the management of rare and threatened species, an important component of model building is the specification of a habitat model describing how a species is related to landscape or bioclimatic variables. Model‐selection uncertainty may arise because there is often a great deal of ambiguity about which habitat model structure best approximates the true underlying biological processes. The standard approach to incorporate habitat models into PVA is to assume the best habitat model is correct, ignoring habitat‐model uncertainty and alternative model structures that may lead to quantitatively different conclusions and management recommendations. Here we provide the first detailed examination of the influence of habitat‐model uncertainty on the ranking of management scenarios from a PVA model. We evaluated and ranked 6 management scenarios for the endangered southern brown bandicoot ( Isoodon obesulus ) with PVA models, each derived from plausible competing habitat models developed with logistic regression. The ranking of management scenarios was sensitive to the choice of the habitat model used in PVA predictions. Our results demonstrate the need to incorporate methods into PVA that better account for model uncertainty and highlight the sensitivity of PVA to decisions made during model building. We recommend that researchers search for and consider a range of habitat models when undertaking model‐based decision making and suggest that routine sensitivity analyses should be expanded to include an analysis of the impact of habitat‐model uncertainty and assumptions.